Station Pipes Inspection Method And Application Based On Damage Modes. Issue 1 (April 2021) - Hai-zhou, Lv; Ming, Sun; Yu-bin, Xu; Yun, Wu; Long-long, Sun
Abstract: Station pipes are important part of the oil and gas delivery system. At present, there are no targeted internal pipeline inspection standards for station pipes. So we can't inspect the station pipes effectively. According to the characteristics of station pipes, this paper introduce the typical damage modes of station pipes, analyze the applicability of common corrosion inspection technology, weld inspection technology, stress corrosion fatigue inspection technology and fatigue damage inspection technology in the inspection of station pipes, propose an inspection method for the station pipes. The field application shows that this inspection method can inspect station pipes effectively, but due to the particularity of station pipes, the method still has some limitations and shortcomings.